Blockchain For Sport: Taekwondo Rate Increase Test - Mulyati, Untung Rahardja, Qurotul Aini (International Journal of Advanced Science and Technology, 2020)
Data management and distributed transactions are characteristic of blockchain. Although the blockchain was originally a technology used for bitcoin. The use of the blockchain spread to many sectors including the sports sector. In Taekwondo Indonesia there is an agenda for the Level Up Examination held in various Cities/Regencies by the Indonesian Taekwondo Branch Management and supervised by the Indonesian Taekwondo Provincial Administrators in the province. Data management, data transactions, and limited data access between the Indonesian Taekwondo Branch Management in a province are obstacles that need to be identified. Dapps using the Vexanium public blockchain is a solution to this problem. With the Vexanium Rate Increase Test data among the Indonesian Taekwondo Branch Officers in the province can be seen transparently and becomes a preventative measure in data loss and data manipulation that often occurs. This research discusses proving the use of Dapps using Vexanium in the Level Up Testing system to be more effective and far more efficient.